Impact Analysis of Window-Wall Ratio on Heating and Cooling Energy Consumption of Residential Buildings in Hot Summer and Cold Winter Zone in China - Qiaoxia Yang; Meng Liu; Chang Shu; Daniel Mmereki; Md. Uzzal Hossain; Xiang Zhan (Journal of Engineering)
In order to assess the optimal window-wall ratio and the proper glazing type in different air conditioning system operation modes of residential buildings for each orientation in three typical cities in hot summer and cold winter zone: Chongqing, Shanghai, and Wuhan simulation models were built and analyzed using Designer’s Simulation Toolkit (DeST). The study analyzed the variation of annual heating energy demand, annual cooling energy demand, and the annual total energy consumption in different conditions, including different orientations, patterns of utilization of air conditioning system, window-wall ratio, and types of windows. The results show that the total energy consumption increased when the window-wall ratio is also increased. It appears more obvious when the window orientation is east or west. Furthermore, in terms of energy efficiency, low-emissivity (Low-E) glass performs better than hollow glass. From this study, it can be concluded that the influence and sensitivity of window-wall ratio on the total energy consumption are related to the operation mode of air conditioning system, the orientation of outside window, and the glazing types of window. The influence of the factors can be regarded as reference mode for the window-wall ratio when designing residential buildings.